For software defined networks on the OMNeT plus plus platform Simulation of OpenFlow protocol - Aksoy, Faruk; Das, Resul (Ieee, 2019)
Software Defined Network (SDN) is a network structure designed to provide effective solutions to adaptation, configuration, scalability and management problems encountered in traditional network structures. Because of its flexible architecture, ease of management and centralized control, software defined networks are replacing traditional networks. The routing rules are transferred from the control plane to the data plane. Openflow is the most common protocol used by the control plane. In this article, using the OMNeT ++ simulation platform, the simulations of the most commonly used openflow protocol in software-defined networks with modules created in NED language are simulated. The performance of the openflow protocol was monitored as a result of the application. The size of the data packets received and transmitted during the communication between the control and data planes and the resulting traffic load can be considered as a disadvantage in software defined networks.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 21-22, 2019 -- Inonu Univ, Malatya, TURKEY
Keywords: Software defined networks; OMNeT plus; open flow; SDN